2005
DOI: 10.1021/ja043521l
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Intermolecular Rhodium-Catalyzed [4 + 2 + 2] Carbocyclization Reactions:  Computational and Experimental Evidence for the Intermediacy of an Alternative Metallacycle Intermediate

Abstract: Intermolecular rhodium-catalyzed [m + n + o] reactions of 1,6-enynes and various pi-components (carbon monoxide, alkynes, 1,3-butadienes, etc.) provide an expeditious approach for the construction of polycyclic fragments that represent important synthons for target-directed synthesis. We present computational and experimental evidence for the existence of a previously undescribed reaction pathway for the rhodium-catalyzed [4 + 2 + 2] reaction involving a 1,6-enyne. This model clearly demonstrates the origin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…In light of the success with the naphthyl substituted 1,6-enyne 10a, we elected to examine other substituents in order to determine the generality of this transformation. 6,11,12 Surprisingly, the extension of this methodology to other C-2 substituted 1,6-enynes, particularly alkyl derivatives, afforded only trace amounts of the product thus indicating that the original catalyst was highly substrate dependent. For example, treatment of the enyne 10b (R = Me) with this catalyst in the presence of 1,3-butadiene, afforded only trace amounts of the carbocycle 11b/12b (<5%).…”
Section: Diastereoselective Rhodium-catalyzed [4+2+2] Carbocyclizatiomentioning
confidence: 97%
“…In light of the success with the naphthyl substituted 1,6-enyne 10a, we elected to examine other substituents in order to determine the generality of this transformation. 6,11,12 Surprisingly, the extension of this methodology to other C-2 substituted 1,6-enynes, particularly alkyl derivatives, afforded only trace amounts of the product thus indicating that the original catalyst was highly substrate dependent. For example, treatment of the enyne 10b (R = Me) with this catalyst in the presence of 1,3-butadiene, afforded only trace amounts of the carbocycle 11b/12b (<5%).…”
Section: Diastereoselective Rhodium-catalyzed [4+2+2] Carbocyclizatiomentioning
confidence: 97%
“…Although the preference for the intermolecular cycloaddition over the intramolecular cyclization at the first stage of the reaction appears improbable, Evans et al suggested the preference for the intermolecular metallacycle formation over the intramolecular metallacycle formation in the Rh-catalyzed [4+2+2] cycloaddition. [29] In this pathway, however, it is necessary to suppose that the insertion and/or the rearrangement of the diene moiety would proceed in highly selective manner, which makes this pathway less likely.…”
Section: Isolation and Reaction Of The Nickel-dienyne Complexesmentioning
confidence: 99%
“…[38] In the following discussion, relative free energies were exclusively employed to analyze the reaction mechanism as done in many excellent publications with regards to the organometallic complexes systems. [39][40][41][42][43][44] It should be kept in mind that the entropy change in the gas phase is much larger than in solution for the association/dissociation transformations, because the translational movement is significantly suppressed in solution. Thus, the entropic contribution to the free energies is remarkably exaggerated and cannot be directly applied to the evaluation of the translational entropy in solution phase.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%